Successful reconstruction of the outflow tract by cervicovaginoplasty: A series of two case reports on sinovaginal bulb or cervicovaginal malformations - Jayanta Biswas; Divyangana Mitra; Lakavath Jyothi; Mallika Datta; Arpita Shankhary; Avijit Bakshi; Arghya Maitra; Kinkar Munian; Somajita Chakraborty; Jhuma Biswas; Atla Sravya (Current Medicine Research and Practice)
Cervicovaginal agenesis, or dysgenesis, in the presence of a normal uterus is a very rare Müllerian anomaly. We report the two cases of unmarried teenage girls who presented with complaints of primary amenorrhoea and cyclical lower abdominal pain. They had normal secondary sexual characteristics with a karyotype of 46XX. They were diagnosed with a blind vagina and a uterus with haematometra and haematosalpinx following clinical and radiological investigations. They underwent vaginoplasty, along with the formation of a neocervix and complete outflow tract reconstruction. On follow-up, their outflow tract remained patent, and they experienced regular menstrual cycles.